Fonsecaeapedrosoi Conidia and Hyphae Activate Neutrophils Distinctly: Requirement of TLR-2 and TLR-4 in Neutrophil Effector Functions - Breda, Leandro Carvalho Dantas; Breda, Cristiane Naffah de Souza; de Almeida, José Roberto Fogaça; Paulo, Larissa Neves Monteiro; Jannuzzi, Grasielle Pereira; Menezes, Isabela de Godoy; Albuquerque, Renata Chaves; Câmara, Niels Olsen Saraiva; Ferreira, Karen Spadari; de Almeida, Sandro Rogério (Frontiers in Immunology, 2020)
Chromoblastomycosis is a chronic and progressive subcutaneous mycosis caused mainly by the fungus Fonsecaea pedrosoi. The infection is characterized by erythaematous papules and the histological sections demonstrating an external layer of fibrous tissue and an internal layer of thick granulomatous inflammatory tissue containing mainly macrophages and neutrophils. Several groups have been studying the roles of the innate and adaptive immune systems in F. pedrosoi infection; however, few studies have focused on the role of neutrophils in this infection. In the current study, we verified the importance of murine neutrophils in the killing of F. pedrosoi conidia and hyphae. We demonstrate that phagocytosis and reactive oxygen species during infection with conidia are TLR-2 and TLR-4-dependent and are essentials for conidial killing. Meanwhile, hyphal killing occurs by NETs formation, in a TLR-2, TLR-4 and ROS-independent manner. In vivo experiments showed that TLR-2 and TLR-4 are also important in Chromoblastomycosis infection. TLR-2KO and TLR-4KO animals had lower levels of MIP-1 and KC chemokines and impaired neutrophil migration to the infected site. These animals also had higher fungal loads during infection with F. pedrosoi conidia, confirming that TLR-2 and TLR-4 are essential receptors for F. pedrosoi recognition and immune system activation. Therefore, this study demonstrated for the first time that neutrophils activation during F. pedrosoi is conidial or hyphal-specific, with TLR-2 and TLR-4 being essential during conidial infection but unnecessary for hyphal killing by neutrophils